FEI Congress on NSAID usage and medication in the equine athlete (FEI, 2010)
Historically the use of medication in equine competition has always attracted controversy, and the use of NSAIDs in particular has given rise to much debate. Prior to 1977, their use in competitions was widespread before a ban was introduced to cover dressage competitions and championships. In 1993, the FEI General Assembly meeting in Rio de Janeiro abolished the use of maximum permitted levels of phenylbutazone. At the 2009 FEI General Assembly, Copenhagen, the ability to use three NSAIDs (phenylbutazone, flunixin meglumine and salicylic acid) was passed, but this was suspended and will be on the agenda again at the FEI General Assembly in November 2010. Under new Equine Anti-Doping and Controlled Medication Regulations (EADCMRs) in force since 5 April 2010, NSAIDs are classified as `Controlled Medicine Substances`. These have a therapeutic role in equine medicine but must not currently exceed pre-determined laboratory screening limits at the time of competition. Screening Limits are levels above which laboratories report a test as being positive; levels that are fair as they are sufficiently high so that traces of substances that are not meaningful do not result in a failed test. Their role in competition horses is still therefore an active subject open to some interpretation and is the focus of the debate at the Congress. The Congress is a central point in the review of the use of NSAIDs in equine competitions, not just for the FEI but for all those with an interest in this area. The culmination of this process is the FEI General Assembly in November 2010, when the issue will be on the agenda. Attendees to the Congress have the opportunity not only to hear the foremost speakers on the subject present their research and expert views, but also to participate in panel discussions, with the purpose of obtaining a full overview on the topic. This approach is intended to allow for the presentation of legal, media and sponsorship views, to add to veterinary and scientific perspectives. Feel free to participate in the times put aside for questions to answer any queries you might have. Please make sure you take the opportunity to meet with experts in their field and hear the various points of view, inside and outside the congress hall.